Effects of SO2 on CO2 capture using chilled ammonia solvent. (August 2017) - Li, Jingde; Cheng, Kuang; Croiset, Eric; Anderson, William A.; Li, Qinghai; Tan, Zhongchao
Highlights: Impact of SO2 on CO2 capture using chilled aqueous ammonia is investigated. A mathematic model based on reaction plane three-film theory is developed. Concentrations of CO2 and SO2 in aqueous ammonia is correlated in a simple equation. The predicted K C O 2 fit well with experimental data in the range of 0–60 °C. Abstract: The impact of SO2 on CO2 capture using chilled aqueous ammonia was investigated in the present study. Experimental observations showed that the mass transfer of CO2 in aqueous ammonia decreased with the increasing concentration of SO2 in the gas phase. A mathematic model based on reaction plane three-film theory was developed and validated to predict the effects of SO2 on CO2 absorption in aqueous ammonia. To make the model more easily used, a simple equation that correlates the concentrations of CO2 and SO2 in chilled aqueous ammonia was proposed based on the numerical results. Although the correlation equation was developed at 0 °C, its prediction for CO2 mass transfer coefficients fit well with experimental data in the temperature range of 0–60 °C.